Correspondence-driven plane-based M3C2 for quantification of 3D topographic change with lower uncertainty [data and source code] - Zahs, Vivien; Winiwarter, Lukas; Anders, Katharina; Williams, Jack G.; Rutzinger, Martin; Bremer, Magnus; Höfle, Bernhard (Universität, 2021)
The analysis and interpretation of 3D topographic change requires methods that achieve low uncertainties in change quantification. Many recent geos...
Gesehen am 02.12.2021
Keywords: Forschungsdaten; Datenbank